Denial of service attack mitigation addressing all the security attributes in OLSR MANET. (2018) - Bhuvaneswari, R.; Ramachandran, R.
Mobile ad hoc network is formed instantly by mobile nodes that exist in a particular radio range. This network because it is infrastructureless can be laid as when and wherever required. The nodes themselves serve as routers to forward the data from source to the destination through multiple hops. The protocols for these ad hoc networks are built such that every node is considered as trustworthy and they work cooperatively among themselves. But in the real environment some nodes are malicious and disrupt the actual communication. In this paper we discuss the security of Optimised Link State Routing protocol (OLSR) for mitigating various active attacks and the role of elliptic curve cryptography and fictitious nodes in strengthening the security attributes.